2021
DOI: 10.3389/feart.2021.689457
|View full text |Cite
|
Sign up to set email alerts
|

Paleoseismological Findings at a New Trench Indicate the 1714 M8.1 Earthquake Ruptured the Main Frontal Thrust Over all the Bhutan Himalaya

Abstract: The 1714 Bhutan earthquake was one of the largest in the Himalaya in the last millennium. We show that the surface rupture caused by this earthquake extended further to the east than previously known, it was at least 175 km long, with slip exceeding 11 m at our study site. The age of the surface rupture was constrained by a combination of radiocarbon and traditional optically stimulated luminescence dating of affected river sediments. Computations using empirical scaling relationships, fitting historical obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…Poor constructed infrastructure and steep topography caused the major devastation in the region during the 2006 and 2011 earthquake events (Rai et al, 2012; Sengupta et al, 2010). In the eastern side, Bhutan region falls in the seismically shadow zone (Gahalaut et al, 2011) and no large detachment earthquakes were reported after 1714 Bhutan Earthquake (Zhao et al, 2021). The 2011 earthquake occurred along the strike‐slip fault, therefore it could not decrease the risk from the terrific Himalayan earthquakes, which can be anticipated to arise at the detachment (Gahalaut, 2011), whereas no large detachment triggered earthquake has occurred after 1100 AD in the Sikkim Himalaya (Kumar et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Poor constructed infrastructure and steep topography caused the major devastation in the region during the 2006 and 2011 earthquake events (Rai et al, 2012; Sengupta et al, 2010). In the eastern side, Bhutan region falls in the seismically shadow zone (Gahalaut et al, 2011) and no large detachment earthquakes were reported after 1714 Bhutan Earthquake (Zhao et al, 2021). The 2011 earthquake occurred along the strike‐slip fault, therefore it could not decrease the risk from the terrific Himalayan earthquakes, which can be anticipated to arise at the detachment (Gahalaut, 2011), whereas no large detachment triggered earthquake has occurred after 1100 AD in the Sikkim Himalaya (Kumar et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Fig.8The historical occurrence of earthquakes in Assam shown in red star(Bhuyan 1933;Gait 1906;Iyengar et al 1999; Ambraseys and Jackson 2003;Rinchen, 1974;Zhao et al 2021; Poddar 1950); OSL dates ofThomas et al 2007 shown in yellow solid rectangle and black solid rectangle shows the ages of the present study. Red solid rectangles indicate the age from Sessa Nalla uplifted section.…”
mentioning
confidence: 82%
“…Fig. 8 The historical occurrence of earthquakes in Assam shown in red star (Bhuyan 1933;Gait 1906;Iyengar et al 1999;Ambraseys and Jackson 2003;Rinchen, 1974;Zhao et al 2021;Poddar 1950)…”
Section: A Field Observation and Back-calculation For Palaeomagnitudementioning
confidence: 99%
“…2 and 5 ) has now been well documented ( 30 , 32 34 ). Amid the large earthquakes that have shaken the Himalayan front in the last three centuries ( 35 ), these two events, as well as the M≈ 8.4, 1934, Bihar/Nepal earthquake ( 36 38 ) and the M≈ 8, 1714, Bhutan Earthquake ( 39 ) ( Fig. 6 C ), are among the few that indisputably ruptured the surface.…”
Section: Geodetic and Seismic Constraints On The Kinematics Of Recent...mentioning
confidence: 99%